A dimensão subjetiva do machismo na educação: significações apreendidas em uma escola de São Paulo no movimento da Pesquisa-Trans-Formação - Mendes, Gislaine Medeiros (2021)
Machismo in this work is treated as a synonym for patriarchal gender relations, a structuring system of relations that promotes gender / gender inequalities which prevents the full development of men and women. Formal education as a fundamental mediation in the constitution of the human can contribute to the process of overcoming inequalities between men and women if it is constituted by a critical conception and oriented towards the collective liberation from exploitation-domination. In view of this, I highlight as a general objective of the research to analyze the Subjective Dimension of machismo in education through the meanings of a group of teachers from a public school in São Paulo apprehended in the Research-Trans-Formation movement, a modality that outlined the planning and the conducting this work that provides for a mutual constitution of researchtraining activities, in a way that one action constituted the other. This research modality is based on the framework of Socio-Historical Psychology and Historical and Dialectical Materialism, a theoretical-methodological approach that guides this study. The information produced was analyzed using the Signification Nucleus procedure. The meanings about machismo in school relations are constituted by mediations such as religion, the political conjuncture, the class as determinant mediations in the production of patriarchal gender relations in education. These mediations determine the objective conditions of the territory and promote an increase in inequalities between men and women. We approach the Subjective Dimension of machismo in education by apprehending that the organization of teaching via public policies for education, the gender ideology and the objective conditions of the school reality constitute the meanings about this phenomenon. Schools located in poor and peripheral territories, which often exercise the role of the State in serving the community as a center of assistance, are constituted by these inequalities. This creates a sense of urgency to overcome these inequalities, so in schools with these characteristics there is a position to confront machismo, which is constituted by moments of paralysis in the face of the possibilities and impossibilities of incorporating this position in the pedagogical practice given the complexity of the phenomena. Ongoing training supported by critical and scientific knowledge emerges as a necessity for the constitution of better ways of coping with sexism at school. The Research-Trans-Formation process may have been an important mediation for the group in the production of new meanings about machismo that surpass meanings that individualize and naturalize the phenomenon. In addition, this process helped to illuminate and highlight good practices and activities aimed at criticizing and overcoming machismo. The analyzes point to the need to further investigate the possible identity relationship between the machismo phenomenon and patriarchal gender relations, which was not possible to show in this work